Expanding subcutaneous mass on the scalp of an immunocompromised woman - Ivan Rodriguez; Karen Lam; Simone Montgomery; Shanice McKenzie; Scott Worswick (Wiley, 2024)
Abstract Acute cutaneous presentations in immunocompromised patients demand careful and thorough evaluation. Here, we present the case of a 26‐year‐old female with acute myeloid leukaemia undergoing salvage chemotherapy, who developed an acutely expanding subcutaneous mass starting on the frontotemporal scalp to the angle of the jaw. Histopathologic evaluation was consistent with sclerosing fat necrosis with overlying psoriasiform spongiotic dermatitis. Tissue cultures revealed multi‐drug resistant Pseudomonas aeruginosa. Given these findings, the patient was diagnosed with infectious panniculitis. This case underscores the necessity of comprehensive diagnostic approaches and multidisciplinary collaboration in managing unusual cutaneous presentations in immunocompromised individuals.